Bone Marrow-Derived CD44+ Cells Migrate to Tissue-Engineered Constructs via SDF-1/CXCR4-JNK Pathway and Aid Bone Repair - Yanzhu Lu; Junchao Xing; Xiaolong Yin; Xiaobo Zhu; Aijun Yang; Jiyue Luo; Jing Gou; Shiwu Dong; Jianzhong Xu; Tianyong Hou (Hindawi Limited, 2019)
Background and Aims. Host-derived cells play crucial roles in the regeneration process of tissue-engineered constructs (TECs) during the treatment of large segmental bone defects (LSBDs). However, their identity, source, and cell recruitment mechanisms remain elusive. Methods. A complex model was created using mice by combining methods of GFP+ bone marrow transplantation (GFP-BMT), parabiosis (GFP+-BMT and wild-type mice), and femoral LSBD, followed by implantation of TECs or DBM scaffolds. Postoperatively, the migration of host BM cells was detected by animal imaging and immunofluorescent staining. Bone repair was evaluated by micro-CT. Signaling pathway repressors including AMD3100 and SP600125 associated with the migration of BM CD44+ cells were further investigated. In vitro, transwell migration and western-blotting assays were performed to verify the related signaling pathway. In vivo, the importance of the SDF-1/CXCR4-JNK pathway was validated by ELISA, fluorescence-activated cell sorting (FACS), immunofluorescent staining, and RT-PCR. Results. First, we found that host cells recruited to facilitate TEC-mediated bone repair were derived from bone marrow and most of them express CD44, indicating the significance of CD44 in the migration of bone marrow cells towards donor MSCs. Then, the predominant roles of SDF-1/CXCR4 and downstream JNK in the migration of BM CD44+ cells towards TECs were demonstrated. Conclusion. Together, we demonstrated that during bone repair promoted by TECs, BM-derived CD44+ cells were essential and their migration towards TECs could be regulated by the SDF-1/CXCR4-JNK signaling pathway.